EXPLORING EQUATIONS BETWEEN ECO-FEMINISM AND THE IDEA OF SUSTAINABLE DEVELOPMENT: SOME REFLECTIONS - Dr. Maitreyee Mukherjee (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Adi Shankaracharya, a Nambudiri Brahmin born in Kerala, India, was not just a proponent but a master of a philosophy of non-dualism called Advaita. His brilliance as a scholar and luminary was evident in his vociferous debates on various philosophical topics in the 8th century. Shankaracharya‟s Vedanta, known as Advaita or non-dualism, is pure, simple, and lucid. Hence, it is sometimes referred to as Kevala-Advaita or unqualified monism. Madhva's dualistic approach, Dvaita Vedanta, contrasts with Adi Shankaracharya's non-dualistic Advaita Vedanta, highlighting the diverse perspectives within Vedanta. Ramanuja's Vishishtadvaita Vedanta, or qualified non-dualism, offers a middle path between dualism and non-dualism, demonstrating the richness of Vedantic thought. Swami Vivekananda, a disciple of Ramakrishna Paramhansa Dev, introduced a practical approach to Advaita Vedanta. His life and work have recently attracted renewed attention, especially after his plenary address at the World Parliament of Religion in Chicago in 1893. This study delves into Adi Shankaracharya‟s Advaita Vedanta, compares various Vedanta traditions, and explores Swami Vivekananda's concept of the importance of applying Advaita Vedanta in daily life, encouraging individuals to realize their true nature as the ultimate reality (Brahman) and manifesting the divinity within.